Analisis Manajemen Pelayanan terhadap Kepuasan Pasien BPJS di Klinik Kesehatan - Maulana, Andika Jaya; Prihandini, Yustin Ari; Sary, Kiki Melda (Jurnal Dunia Kesmas, 2024)
Pharmacy is service facility used for pharmacy practice by pharmacists. Health service standards are guidelines used to provide pharmaceutical services. The quality of pharmaceutical services is related to patient satisfaction. The purpose of this study was to determine the quality of pharmaceutical services, to determine the level of satisfaction of BPJS participants and the relationship between the quality of pharmaceutical services at the X Martapura Pharmacy Clinic. This study with a cross sectional survey design conducted on BPJS patients who visit the X Martapura Pharmacy Clinic. The sample used in the study was 70 person using purposive sampling technique. Data was collected using a 5-dimensional SERVQUAL method questionnaire, namely: assurance, tangible, responsiveness, empathy and reliability. Data analysis using Chi Square test. The results of the research that have been carried out can be seen that the overall quality of pharmaceutical services at the Martapura Pharmacy Clinic is categorized as very important and the level of patient satisfaction is categorized as very satisfied. The relationship between the quality of pharmaceutical services and the level of satisfaction of BPJS participants obtained a p-value of 0.000, which means that there is relationship between the quality of pharmaceutical services and the satisfaction level of BPJS participants at the Martapura Clinic Pharmacy.